Respon Gereja Atas Pandemik Coronavirus Disease 2019 Dan Ibadah Rumah - Roedy Silitonga (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
The church is present on earth as an extension of the presence of the kingdom of God among humanity. The church is always present to respond to the conditions and situations of the times in a variety of challenges and temptations. But the church always sided with God's sovereignty and will govern and control everything, including the pandemics experienced by humans on this earth. The Church, currently dealing directly with the Covid-19 pandemic, which has worldwide, and its spread is so massive, and its impact is so wide in various sectors of life. The church was sent to bring the peace of Christ in truth and love. That is why the church responds to the appeal of the Government and health protocols from WHO by carrying out church services at home. Worship at home is not an attempt to establish a house church as a new institution. Worship at home is a form of faith that is responsible for the lives of fellow humans, and at the same time as an expression of love for others. Home worship is a service that is held based on the worship and liturgy of a church institution, where the congregation is part of its members. Principles and mechanisms of worship at home are regulated in such a way that using all available and available digital equipment and technology. The important and most important thing in conducting worship at home is that the congregation continues to truly worship the Triune God, sing praises to God, pray, and the peak and center is to listen to the word of God through preaching live (live streaming) or in recorded form or in printed form.